Analisis Deteksi Dini Tumbuh Kembang Balita dengan Penggunaan Kuesioner Pra Skrining Perkembangan (KPSP) di RT.003 RW.003 Kel. Bukit Baru, Kec. Ilir Barat I, Palembang - Fristika, Yessy Octa (NHM PRESS, 2024)
Early detection of growth and development is very important to determine a child's growth and development if the child experiences delays. To see the growth and development of young children based on their age, they can be stimulated or create educational games or learning media that are adapted to the child's age and characteristics or you can also assess the child's growth and development using the Pre-Developmental Screening Questionnaire (KPSP). KPSP is an early detection instrument in child development which is useful for determining whether a child's development is normal or whether there are deviations. This research aims to look at the Analysis of Early Detection of Toddler Growth and Development using the Pre-Developmental Screening Questionnaire (KPSP) in RT.003 RW.003 Kel. Bukit Baru, Kec. Ilir Barat I, Palembang. This research method uses a quantitative descriptive design using primary data using a cross sectional approach. The analysis used is univariate and bivariate. The research samples taken were toddlers aged 3 months - 60 months by Total Sampling. The number of samples in this study was 27 samples, the degree of confidence was 95% using chi square. The results of the chi square statistical test obtained a value of P-Value = 0.001 (P-Value < α), meaning that at α = 5% it shows that there is a significant relationship between Early Detection of Toddler Growth and Development and the Use of the Pre-Developmental Screening Questionnaire (KPSP) P- Value = 0.001 (P-Value < α), meaning at α = 5% and OR = 0.087 (95% CI: 0.023 – 0.327). This research advises mothers who have toddlers to improve health information, especially about early detection of toddler growth and development and for students to increase knowledge about excellent service in midwifery care for neonates, infants and toddlers, especially in detecting early growth and development of children through the Pre-Developmental Screening Questionnaire. (KPSP).